United States and China in power transition - "Strategic Studies Institute, USA" (New Delhi, 2013)
In a world of independent sovereign nations, there is always an uneven distribution of power some nations are more powerful than others, differentiated by their size and level of development. Throughout history, changes in the balance of power and efforts to keep or alter the international order have led to struggles among the big nations and set the stage for great power wars. This book discusses a wide range of issues affecting the US-China relations in the context of an ongoing power transition between these two great powers the rise of China and its impact during its rising approach to modernity and the future of the US-China power transition considering the future of international relations. The author has taken painstaking care to put the conflicting positions in true perspective. His intent is to analyze the parochial positions of both the countries so that constructive measures can be taken by their leaders, to maintain international relations in seminal ways in the years to come. Various international treaties and conventions have been appended to enhance the utility of the book.
Keywords: "International relations, United states an China internat"